Effective Degradation of Gluten and Its Fragments by Gluten-Specific Peptidases: A Review on Application for the Treatment of Patients with Gluten Sensitivity - Yakov E. Dunaevsky; Valeriia F. Tereshchenkova; Mikhail A. Belozersky; Irina Y. Filippova; Brenda Oppert; Elena N. Elpidina (MDPI AG, 2021)
To date, there is no effective treatment for celiac disease (CD, gluten enteropathy), an autoimmune disease caused by gluten-containing food. Celiac patients are supported by a strict gluten-free diet (GFD). However, in some cases GFD does not negate gluten-induced symptoms. Many patients with CD, despite following such a diet, retain symptoms of active disease due to high sensitivity even to traces of gluten. In addition, strict adherence to GFD reduces the quality of life of patients, as often it is difficult to maintain in a professional or social environment. Various pharmacological treatments are being developed to complement GFD. One promising treatment is enzyme therapy, involving the intake of peptidases with food to digest immunogenic gluten peptides that are resistant to hydrolysis due to a high prevalence of proline and glutamine amino acids. This narrative review considers the features of the main proline/glutamine-rich proteins of cereals and the conditions that cause the symptoms of CD. In addition, we evaluate information about peptidases from various sources that can effectively break down these proteins and their immunogenic peptides, and analyze data on their activity and preliminary clinical trials. Thus far, the data suggest that enzyme therapy alone is not sufficient for the treatment of CD but can be used as a pharmacological supplement to GFD.